Engaging Stakeholders in the Design and Conduct of Embedded Pragmatic Clinical Trials for Alzheimer's Disease and Alzheimer's Disease–Related Dementias. (26th June 2020) - Harrison, Jill; Maslow, Katie; Tambor, Ellen; Phillips, Louise; Frank, Lori; Herndon, Laurie; Epstein‐Lubow, Gary
Abstract : Embedded pragmatic clinical trials (ePCTs) of nondrug interventions for Alzheimer's disease and Alzheimer's disease–related dementias (AD/ADRD) are conducted in real‐world clinical settings and designed to generate an evidence base to inform clinical and policy decisions about care for this vulnerable population. The ePCTs exist within a complex ecosystem of relationships between researchers, payors, policymakers, healthcare systems, direct care staff, advocacy groups, families, caregivers, and people living with dementia (PLWD). Because the rapid increase of the number of Americans with AD/ADRD outpaces curative treatments, there is an urgent need to mobilize the power of these relationships to improve dementia care and address a mounting public health crisis. Stakeholder engagement in ePCTs is essential to generate research questions, establish the relevancy of trials to the intended end users, and understand the factors that influence dissemination and implementation in real‐world clinical settings. The process of including stakeholders in ePCTs for dementia is similar to stakeholder engagement in ePCTs for other diseases and conditions; however, the unique nature of embedded research, prevalence of caregiver and provider burden, and the progressive worsening of cognitive impairment in PLWD must be approached with additional strategies. This article presents key considerations of stakeholder engagement for ePCTs in AD/ADRD and main activities of the stakeholder engagement team in the National Institute on Aging IMPACT Collaboratory to move the field forward. J Am Geriatr Soc 68:S62–S67, 2020 .